UTILIZING TIRE AND CARDBOARD JUMP METHOD TO IMPROVE LONG JUMP STYLE OF SQUATTING ABILITY OF IV GRADE STUDENTS AT SD NEGERI 43 PALEMBANG - I Bagus Endrawan; Sasmarianto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The type of this study was a class action research aiming at determining the improvement of students’ long jump style of squatting ability by using tire and cardboard jump at fourth grade of SD Negeri 43 Palembang. The subjects of the study were 32 students consisting of 15 male students and 17 female students at the fourth grade. Data were collected through observation and test. The learning process was conducted in several cycles in order that students could reach the Minimum Provision Criteria (KKM) established by the school. The results of the test revealed that 16 students were complete (50% of the students reached KKM) in the pre-cycle. Meanwhile, the results of the test in cycle I found that 20 students reached the KKM (62.5%). Then, in cycle II, the number of students who passed the test increased to 26 students (81.25%), and in cycle III, all students reached KKM (100%). Thus, it could be concluded that the method of tire and cardboard jump improved the students’ learning outcomes in long jump style of squatting at SD Negeri 43 Palembang.